The relationship between social support and academic engagement among university students: the chain mediating effects of life satisfaction and academic motivation - Chunmei Chen; Fei Bian; Yujie Zhu (BMC, 2023)
Abstract Background University students' academic engagement has a significant impact on their academic performance and career development. Methods In order to explore the influential mechanisms of social support on university students' academic engagement and the mediating role of academic motivation and life satisfaction, this study used the Adolescent Social Support Scale, University Students' Academic Engagement Scale Questionnaire, Adolescent Student Life Satisfaction Scale and University Students' Academic Motivation Questionnaire, to conduct a questionnaire survey and empirical analysis on 2106 Chinese university students. Results (1) social support significantly and positively predicts academic engagement; (2) social support influences academic engagement through the mediating effect of life satisfaction; (3) social support influences academic engagement through the mediating effect of academic motivation; (4) life satisfaction and academic motivation play a chain mediating role in the effect of social support on academic engagement. Conclusions This study contributes to understanding the underlying mechanisms of the relationship between social support and academic engagement, which in turn provides insights for universities and the departments concerned to make measures to improve the level of university students' academic engagement.